Reumatoid Factor Examination in Thalassemia Patients - Doni Setiawan; Via Oktaviani Hiytulmadani; Atun Farihatun (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background & Objective Patients with thalassaemia major with severe anaemia must receive blood transfusions for life. Giving continuous blood transfusions can cause iron accumulation in body tissues so that it can conclude complications, one of which is rheumatoid arthritis due to iron deposition in synovial tissue. This study is to determine the results of rheumatoid factor examination in thalassaemia patients with blood transfusion therapy. Method the research used is descriptive. The sampling technique uses incidental with a large number of samples as many as 66. Result Based on the results of the study obtained positive results as many as 11 (17%) people with an average Rheumatoid Factor level of 29 IU/mL, and negative results as many as 55 (83%) people. Conclusion Thalassaemia patients with blood transfusion therapy show the risk of rheumatoid arthritis with positive results of rheumatoid factor examination.